Markup responses to Chinese imports - Philipp Meinen (Deutsche Bundesbank, 2016)
This paper analyzes markup responses of Danish firms to Chinese imports. Besides negative markup responses due to competitive pressure, we present some evidence for marginal cost savings related to Chinese intermediate goods imports which tend to raise firm-level markups.
Keywords: D22; F14; L25; 330; Chinese Imports; Markups